Analysis of the scientific production on Down Syndrome (Research, Society and Development, 2022)
Introduction: The object of this study is to understand the scientific production on Down Syndrome (DS) in Nursing journals. Down Syndrome is a genetic condition that causes chromosome alterations and was discovered by the English physician John Langdon Down, who named it trisomy 21. Objective: to analyze the scientific production on Down Syndrome in the period 2011-2022 in Brazil. Method: This is an integrative literature review based on scientific articles about this condition, published in Brazilian nursing journals with QUALIS A1 to B3, covering primary and secondary data research. Seven scientific articles were selected and analyzed. Resultados/Discussão: 2013 was the year with the highest number of publications about this syndrome, as for the title of the authors in the articles, most had the participation of masters, doctors and teachers. Regarding the federative state, most were concentrated in the Northeast region, with qualitative approach most. The main difficulty reported in the articles by professionals was the management with this diagnosis in relation to the family and client. Conclusion: There are few articles published in the nursing field about Down Syndrome, a fact evidenced by the low production over 10 years of publication in journals. The production of new scientific works is proposed, since they are fundamental for professionals to update themselves with new knowledge, as well as to be led to an assistance that aims at the perspective of the family together with the patient regarding his future and the importance of the multidisciplinary team's performance in the development of children with Down Syndrome.